MODIFICATION OF CONVENTIONAL LASER-ASSISTED UVULOPALATOPLASTY PROCEDURE - Suzuki, Kana; Tomoda, Koichi; Shimode, Yuzo; Takashima, Masayuki; Yoshida, Hajime (JIBI INKOKA TEMBO, 2002)
Over a three-year period, we have treated 174 patients for snoring and obstructive sleep apnea syn-drome (OSAS) using laser-assisted uvulopalatoplasty (LAUP). However, postoperative sclerosis of the soft palate as a result of wound healing is a common complication of conventional LAUP. We have modified the conventional LAUP method by preserving the intact mucosal tissue and suturing it on the lateral side using a special device known as “MANICEPS ® ”. This technique dramatically reduces the incidence of postoperative stenosis in the oropharyngeal space as well as postoperative bleeding. This method is especially useful for the out-patient treatment of patients with snoring and mild OSAS.